Canada's Arctic waters in international law / Donat Pharand. - Pharand, Donat (Studies in polar research., 1988)
The crossing of the Northwest Passage in August 1985 by a US icebreaker, without requesting authorisation, raised the whole question of Canada's sovereignty over the waters of its Arctic Archipelago. Given this controversy and the existence of similar situations in other parts of the world, this book presents an examination of the international legal validity of Canada's claim by an in-depth study of three possible bases in international law: the sector theory, the doctrine of historic waters and the Straight baseline system. This work is the second of a series of monographs arising from the Canadian Northern Waters Project of the Dalhousie Ocean Studies Programme, It draws on examples from other parts of the world, and, as such it will have relevance beyond the development of the Canadian Arctic. Professor Pharand is a recognised authority in this field. His earlier book, The Law of the Sea of the Arctic is still one of the standard reference works in the area, but with changes in the general law of the sea, this monograph presents a timely reappraisal of the relevant legal theories and practices.